Does tourist’s engagement influence destination loyalty? An analysis of Turismo do Centro de Portugal - Freitas, C. C. de.; Bilro, R. G. (TOURMAN 2021 Book of Abstracts - 4th International Scientific Conference, 2021)
Nowadays, the tourism market is facing several challenges and becoming an even more competitive environment. Destination competitiveness is flourishing not only because of the impact on destinations due to the tourism growth but also due to COVID -19 restrictions. The need to have a distinctive factor for destinations is now more critical than ever, and destinations should aim to create a relationship with tourists to ensure the experience is memorable and that tourists repeat the visit and make positive recommendations about the destination to others. This need suggests the usefulness of tourist engagement to achieve their goals ultimately. So, this study aims to understand how the engagement between tourists and the tourism destination can influence tourists’ destination loyalty, namely their willingness to recommend the destination to friends and family and their intention to repeat the visit. This research explores Centro de Portugal (a relevant destination in Portugal) as the loyal destination.